PENDAMPINGAN REMAJA PUTRI DALAM EDUKASI KESEHATAN REPRODUKSI DI DESA CAMPAKA KECAMATAN PASONGSONGAN - Dian Permatasari; Emdat Suprayitno; Rasyidah Rasyidah; Cory Nelia Damayanti; Abd Wahid (LPPM Universitas Bina Bangsa, 2022)
Reproductive health is a state of well-being of every individual in terms of physical, mental, and social. Reproductive health services aim to provide professional and professional services to adolescents. Another objective is to give women confidence in their reproductive health and to be able to maintain excellent and healthy reproductive health, meaning that they are responsible for their health. In this study, using a quasi-experimental one-group pretest-posttest design, 28 respondents used a questionnaire, the pretest was given a questionnaire, and intervention was given in the form of counseling. An evaluation was carried out, after which another questionnaire was given, namely the post-test. The results showed that the level of knowledge was good, as much as 20%, and after being given education, the results of the post-test, namely good knowledge, reached 58.9%. The conclusion is that there is an increase in knowledge from the results of the pretest and post-test, where the results of the respondents' evaluation are very enthusiastic and the education provided is smooth